2016
DOI: 10.3389/fpls.2016.00500
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Integrated Pest Management in GM Cotton Systems Using Host Plant Resistance

Abstract: Cotton has lost many ancestral defensive traits against key invertebrate pests. This is suggested by the levels of resistance to some pests found in wild cotton genotypes as well as in cultivated landraces and is a result of domestication and a long history of targeted breeding for yield and fiber quality, along with the capacity to control pests with pesticides. Genetic modification (GM) allowed integration of toxins from a bacteria into cotton to control key Lepidopteran pests. Since the mid-1990s, use of GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 124 publications
(162 reference statements)
0
45
0
Order By: Relevance
“…Cotton bollworm (Helicoverpa armigera), once thought to be the most serious insect pest of cotton, has been well controlled by the widely planted Bt cotton (Wu et al, 2008). However, some new challenges have emerged: continuously planted mono-Bt cotton can lead to pest resistance; and in fields planted with Bt cotton, the decreased spraying of pesticides may result in non-Bt-targeted pests becoming new key pests, particularly piercing-sucking insects (Wu et al, 2008;Trapero et al, 2016).…”
mentioning
confidence: 99%
“…Cotton bollworm (Helicoverpa armigera), once thought to be the most serious insect pest of cotton, has been well controlled by the widely planted Bt cotton (Wu et al, 2008). However, some new challenges have emerged: continuously planted mono-Bt cotton can lead to pest resistance; and in fields planted with Bt cotton, the decreased spraying of pesticides may result in non-Bt-targeted pests becoming new key pests, particularly piercing-sucking insects (Wu et al, 2008;Trapero et al, 2016).…”
mentioning
confidence: 99%
“…Balakrishnan (2006) reported that constitutive allelochemical components, such as gossypol or condensed tannin, showed a negative significant relationship with thrips population development. It is likely that domestication and selection for yield and fibre quality traits along with desirable agronomic traits in cotton has resulted in limited genetic diversity in elite commercial cotton varieties (Trapero et al, 2016). Further, the availability of insecticides, and now GM-cotton with pest resistance, reduces the need for plant defences against pests.…”
Section: Plant Resistance To Thrips 37mentioning
confidence: 99%
“…We also included another tetraploid cotton species, G. barbadense, in which resistance has been reported against thrips (Zhang et al, 2013). We Resistance to other pests (e.g., mites, whiteflies) Miyazaki et al (2012Miyazaki et al ( , 2013a included the diploid species G. arboreum, G. thurberi, and G. trilobum, as they have been reported to have resistance against other cotton pests (Trapero et al, 2016). We assessed plant resistance over four cotton seasons, from 2010 to 2014, in the field by counting the thrips and measuring the amount of leaf damage and the plant dry weight for each genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing cotton pest management using plant natural defenses has been described as a promising way to improve the management of insect pests . Induction of plant defenses is one of the pathways that is currently being explored .…”
Section: Introductionmentioning
confidence: 99%